Prevalence of neonatal near miss and associated factors in Nepal: a cross-sectional study - Rajbanshi Sushma; Mohd Noor Norhayati; Nik Hussain Nik Hazlina (BMC, 2021)
Abstract Background The rate of neonatal mortality has declined but lesser than the infant mortality rate and remains a major public health challenge in low- and middle-income countries. There is an urgent need to focus on newborn care, especially during the first 24 h after birth and the early neonatal period. Neonatal near miss (NNM) is an emerging concept similar to that of maternal near miss. NNM events occur three to eight times more often than neonatal deaths. The objective of this study was to establish the prevalence of NNM and identify its associated factors. Methods A hospital-based cross-sectional study was conducted in Koshi Hospital, Morang district, Nepal. Neonates and their mothers of unspecified maternal age and gestational age were enrolled. Key inclusion criteria were pragmatic and management markers of NNM and admission of newborn infants to the neonatal intensive care unit (NICU) in Koshi Hospital. Non-Nepali citizens were excluded. Consecutive sampling was used until the required sample size of 1,000 newborn infants was reached. Simple and multiple logistic regression was performed using SPSS® version 24.0. Results One thousand respondents were recruited. The prevalence of NNM was 79 per 1,000 live births. Severe maternal morbidity (adjusted odds ratio (aOR) 4.52; 95% confidence interval (CI) 2.07-9.84) and no formal education (aOR 2.16; 95% CI 1.12-4.14) had a positive association with NNM, while multiparity (aOR 0.52; 95% CI 0.32-0.86) and caesarean section (aOR 0.44; 95% CI 0.19-0.99) had negative associations with NNM. Conclusions Maternal characteristics and complications were associated with NNM. Healthcare providers should be aware of the impact of obstetric factors on newborn health and provide earlier interventions to pregnant women, thus increasing survival chances of newborns.